Infanticide in Peruvian law - Avendaño, Leonidas (1922)
Communication to the First National Conference of the Peruvian Child, by Dr. Leonidas Avendaño, Professor of Legal Medicine at the Faculty of Medicine, Member of the Academy of Medicine of Lima.